2018
DOI: 10.1111/jocn.14183
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the delivery of the fundamentals of care: Perceptions of nurses, nursing leaders and healthcare consumers

Abstract: Nurses and consumers share a common perspective of the factors influencing the delivery of the fundamentals of care and both value a therapeutic nurse-patient relationship. Clinical nursing leaders must understand the impact of their role in shaping the delivery of the fundamentals of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…Most nurses focused their tasks and communications mainly on physical care and did not explicitly incorporate elements of psychosocial care, even though results show that there was plenty of opportunity within the nurse–patient interaction to do so, confirming that such care does not take up more time or resources (McCabe, ). Even though nurses perceive a lack of time as a barrier for patient involvement (van Belle et al, ; Tobiano et al, ) and integrated care (Conroy, ), McCabe () further demonstrated that nurses do not communicate sufficiently in a patient‐centred way even when they have the opportunity to do so, and that patients perceive nurses in general as being more aimed at task completion than on communicating (McCabe, ). Physical care then becomes more of an act, rather than an opportunity to connect with a patient as a means to provide patient‐centred care (Feo & Kitson, ), even though the quality of the relationship between the nurse and the patient is significantly linked to improved health outcomes such as symptom relief and improvements in clinical and functional status (Safran, Miller, & Beckman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most nurses focused their tasks and communications mainly on physical care and did not explicitly incorporate elements of psychosocial care, even though results show that there was plenty of opportunity within the nurse–patient interaction to do so, confirming that such care does not take up more time or resources (McCabe, ). Even though nurses perceive a lack of time as a barrier for patient involvement (van Belle et al, ; Tobiano et al, ) and integrated care (Conroy, ), McCabe () further demonstrated that nurses do not communicate sufficiently in a patient‐centred way even when they have the opportunity to do so, and that patients perceive nurses in general as being more aimed at task completion than on communicating (McCabe, ). Physical care then becomes more of an act, rather than an opportunity to connect with a patient as a means to provide patient‐centred care (Feo & Kitson, ), even though the quality of the relationship between the nurse and the patient is significantly linked to improved health outcomes such as symptom relief and improvements in clinical and functional status (Safran, Miller, & Beckman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Culture has many manifestations. According to Conroy (2018), nurse leaders recognise how hospital culture carries implied relationships of trust of the healthcare professional. They warn how hospital patients are reticent to speak out because of the unquestioned trust in the nurse–patient relationship.…”
Section: Building Trusting Relationshipsmentioning
confidence: 99%
“…How fundamental care is “done” is being measured (Parr, Bell, & Koziol‐McLain, 2018) in two district health boards (DHBs), and there is a growing emphasis on patient stories and experience measures to help organisations “own” the care that is delivered. Researchers across Australia and New Zealand are actively researching the fundamentals of care and have published their findings (Conroy, 2018; Feo, Frensham, Conroy, & Kitson, 2019; Kitson, 2018; Minton, Batten, & Huntington, 2018). However, questions remain about why the fundamentals of care are still not delivered in a safe, consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…This discursive paper is based on the FOC framework literature (Feo, Conroy, et al, ; Kitson, ; Kitson, Conroy, et al, ) and on the proposed FOC‐PP (Feo, Conroy, Alderman, et al, ). Several articles on the FOC framework have used clinical scenarios to illustrate the framework (Conroy, ; Feo, Conroy, Alderman, et al, ; Feo, Rasmussen, et al, ; Kitson, ). This article presents a clinical scenario that develops through the five stages of the FOC‐PP.…”
Section: Designmentioning
confidence: 99%